2020
DOI: 10.1007/s42452-020-03586-1
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of concrete reinforced steel corrosion by penta sodium triphosphate: physicochemical and electrochemical investigations

Abstract: The capacity of penta sodium triphosphate (PST) to avert the steel reinforcement corrosion in contaminated concrete by NaCl was investigated for 480 days using electrochemical impedance spectroscopy, potentiodynamic polarization, half-cell potential and gravimetric methods. The mechanism of interaction of PST molecules and the changes took place on the steel surface assessed using spectroscopic and microscopic analysis. Compression tests of the concrete specimens were performed to monitor the strength of concr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…More recently, the use of alternative pentasodium triphosphate compounds Na 5 P 3 O 10 , also known as sodium tripolyphospate, has shown an increased inhibition efficiency of around 80% for 480 days exposure in 3.5% NaCl, which is attributed to the development of a protective film barrier of PST on the steel rebar surface. Potentiodynamic polarization results revealed that PST affects the anodic and cathodic sites uniformly, thus presenting a mixed-type corrosion-inhibitor protection mechanism [54]. The use of inorganic corrosioninhibitor mixtures containing hexametaphosphate compounds (NaPO 3 ) 6 , used in 3.5% NaCl contained SCPS, have been proven to reduce the corrosion rate by 8.60 and 25.52 times for 3 and 5% inhibitor addition, respectively [55].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the use of alternative pentasodium triphosphate compounds Na 5 P 3 O 10 , also known as sodium tripolyphospate, has shown an increased inhibition efficiency of around 80% for 480 days exposure in 3.5% NaCl, which is attributed to the development of a protective film barrier of PST on the steel rebar surface. Potentiodynamic polarization results revealed that PST affects the anodic and cathodic sites uniformly, thus presenting a mixed-type corrosion-inhibitor protection mechanism [54]. The use of inorganic corrosioninhibitor mixtures containing hexametaphosphate compounds (NaPO 3 ) 6 , used in 3.5% NaCl contained SCPS, have been proven to reduce the corrosion rate by 8.60 and 25.52 times for 3 and 5% inhibitor addition, respectively [55].…”
Section: Introductionmentioning
confidence: 99%
“…[68] These plant constituents are responsible for the formation of stable diffusion-barrier layers on the steel surface by an adsorption mechanism that isolates the steel from the corrosive concrete environments. [69,70] Consequently, the extent of corrosion level of the SRC infrastructures extended for a long time.…”
Section: Inhibitory Potentiality Of Cement-based Additivesmentioning
confidence: 99%
“…It is also known that the formation of hydrated iron oxide and pitting corrosion of chlorides, sulfates, uorides, nitrates, and so forth expands steel bars, generating internal pressure in the surrounding concrete, which in turn causes structural degradation in the carcass of the buildings 43 . To overcome this drawback, micro lament steel (MS) bers with low ber content are incorporated into concrete 44 .…”
Section: Introductionmentioning
confidence: 99%